INNOVATIONS IN ELT PROGRAMME DEVELOPMENT: BUILDING STRONG FOUNDATIONS WITH LEARNER AUTONOMY - Alsagoff, Lubna (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2016)
In this paper, I share some experiences about how we, at the National Institute of Education (NIE), Singapore, addressed a challenge with regard to our student teachers’ English language standards. This problem, identified by our Ministry of Education, was a continuing one that seemed difficult to resolve. We reanalyzed the issues and saw that a different perspective was needed. Thus, we moved away from the traditionally-oriented language proficiency courses that had been running at NIE and instead developed a language programme that placed learnerautonomy as a central pedagogical tenet. We sought to create motivated, autonomous learners who were able to appreciate and understand the complexity of the issues, develop their own understandings, and achieve the the learning goals.